Opportunities and challenges in the management of celiac disease in Asia - Agarwal, Ashish (JGH Open, 2020)
Although once considered uncommon, there is increasing recognition of celiac disease (CeD) in Asia. It is now clear that CeD is a disorder as frequent in certain Asian countries as that in western countries, although it often remains undiagnosed. With increasing awareness and diagnosis, the absolute numbers of celiac patients are expected to increase markedly in Asia. Asia, with 60% of the population of the world, is probably the major “reservoir” of undiagnosed CeD in the world. As Asia has a huge landscape along with highly heterogenous genetic, social, cultural, and nutritional practices, similar heterogeneity is seen in the epidemiology, diagnostic, and therapeutic facilities for CeD in Asia. In this article, we have reviewed the changes in the epidemiology, diagnostics, and management of CeD in Asia and summarized the challenges and opportunities for its emergence in Asia.